Long-term changes of renal function in relation to ace inhibitor/angiotensin receptor blocker dosing in patients with heart failure and chronic kidney disease - Fröhlich, Hanna; Nelges, Christoph; Täger, Tobias; Schwenger, Vedat; Cebola, Rita; Schnorbach, Johannes; Goode, Kevin M.; Kazmi, Syed; Katus, Hugo; Cleland, John G. F.; Clark, Andrew L.; Frankenstein, Lutz (American heart journal, 2016)
Background - Angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) have become cornerstones of therapy for chronic heart failure (CHF). Guidelines advise high target doses for ACEIs/ARBs, but fear of worsening renal function may limit dose titration in patients with concomitant chronic kidney disease (CKD). - Methods - In this retrospective observational study, we identified 722 consecutive patients with systolic CHF, stable CKD stage III/IV (estimated glomerular filtration rate [eGFR] 15-60 mL min−1 1.73 m−2) and chronic ACEI/ARB treatment from the outpatient heart failure clinics at the Universities of Hull, UK, and Heidelberg, Germany. Change of renal function, worsening CHF, and hyperkalemia at 12-month follow-up were analyzed as a function of both baseline ACEI/ARB dose and dose change from baseline. - Results - ΔeGFR was not related to baseline dose of ACEI/ARB (P = .58), or to relative (P = .18) or absolute change of ACEI/ARB dose (P = .21) during follow-up. Expressing change of renal function as a categorical variable (improved/stable/decreased) as well as subgroup analyses with respect to age, sex, New York Heart Association functional class, left ventricular ejection fraction, diabetes, concomitant aldosterone antagonists, CKD stage, hypertension, ACEI vs ARB, and congestion status yielded similar results. There was no association of dose/dose change with incidence of either worsening CHF or hyperkalemia. - Conclusions - In patients with systolic CHF and stable CKD stage III/IV, neither continuation of high doses of ACEI/ARB nor up-titration was related to adverse changes in longer-term renal function. Conversely, down-titration was not associated with improvement in eGFR. Use of high doses of ACEI/ARB and their up-titration in patients with CHF and CKD III/IV may be appropriate provided that the patient is adequately monitored.
Gesehen am 28.05.2020